The Perception of Civilization and Savageness: Aldous Huxley’s Brave New World - Arif , Saffeen N. (Research Highlights in Language, Literature and Education Vol. 9, 2023)
The objective of this article is to explore Aldous Huxley’s Brave New World (1932) in terms of the nature of the rules – which are presumably civilized – by which the World State citizens in the story have to abide. Those rules are, characteristically, at odds with the usual human ways of life that are referred to as “savage”. The main argument raised here is socially and culturally oriented; the society of this World State seemingly provides every materialistic thing for its members, yet it remains far away from idealism. The article, thus, attempts to examine the reasons behind the failure of this civilization, which is fundamentally based on scientific and technological advancement. The article, moreover, aims to explore and analyze the two concepts of civilization and savageness as far as Huxley's utopian/dystopian world is concerned, trying to underscore, utilizing juxtaposing the discussion of the two concepts, how the two are perceived and what ironical undertones there are underlying their true meanings.